Astroglia and Tau: New Perspectives - Kovacs, Gabor G. (Frontiers in Aging Neuroscience, 2020)
The role of astrocytes in the pathogenesis of neurodegenerative proteinopathies is explored as contributors to neuronal degeneration or neuroprotection, and also as potential mediators of the transcellular propagation or elimination of disease-associated proteins. Although protein astrogliopathies can be observed in different forms of neurodegenerative conditions, morphological characterization of protein astrogliopathy is considered only for the neuropathological diagnosis and classification of tauopathies. Currently, there is emerging consensus that at least six types of astrocytic tau pathologies should be distinguished. Tufted astrocytes, astrocytic plaques, ramified astrocytes, and globular astroglial inclusions are seen mostly in primary tauopathies, while thorn-shaped astrocytes and granular/fuzzy astrocytes are discussed in the context of ageing-related tau astrogliopathy (ARTAG). ARTAG can be seen in subpial, subependymal, perivascular, and white and gray matter locations, some overlapping with the features of tau pathology seen in chronic traumatic encephalopathy. Furthermore, gray matter ARTAG shares features with primary tauopathy-related astrocytic tau pathology. Sequential distribution patterns have been described for tau astrogliopathies. Importantly, astrocytic tau pathology in primary tauopathies can be observed in brain areas without neuronal tau deposition. The various morphologies of tau astrogliopathy might reflect a role in the propagation of pathological tau protein, an early response to a yet unidentified neurodegeneration-inducing event, or, particularly for ARTAG, a response to a long-term or repeated pathogenic process such as blood brain barrier dysfunction or local mechanical impact. The concept of tau astrogliopathies and ARTAG facilitated communication among research disciplines and stimulated additional exploration of the significance of astrocytic lesions in neurodegenerative conditions.